High numbers of mobilized CD34+ cells collected in AML in first remission are associated with high relapse risk irrespective of treatment with autologous peripheral blood SCT or autologous BMT - Hengeveld, M; Suciu, S; Chelgoum, Y; Marie, J-P; Muus, P; Lefrère, F; Mandelli, F; Pane, F; Amadori, S; Fioritoni, G; Labar, B; Baron, F; et al. (Bone marrow transplantation, 2015)
The faster hematopoietic recovery after autologous peripheral blood SCT (APBSCT) in patients with AML may be offset by an increased relapse risk as compared with autologous BMT (ABMT). The EORTC and GIMEMA Leukemia Groups conducted a trial (AML-10) in which they compared, as second randomization, APBSCT and ABMT in first CR patients without an HLA compatible donor. A total of 292 patients were randomized. The 5-year DFS rate was 41% in the APBSCT arm and 46% in the ABMT arm with a hazard ratio (HR) of 1.17; 95% confidence interval=0.85-1.59; P=0.34. The 5-year cumulative relapse incidence was 56% vs 49% (P=0.26), and the 5-year OS 50% and 55% (P=0.6) in the APBSCT and ABMT groups, respectively. APBSCT was associated with significantly faster recovery of neutrophils and platelets, shorter duration of hospitalization, reduced need of transfusion packed RBC and less days of intravenous antibiotics. In both treatment groups, higher numbers of mobilized CD34+ cells were associated with a significantly higher relapse risk irrespective of the treatment given after the mobilization. Randomization between APBSCT and ABMT did not result in significantly different outcomes in terms of DFS, OS and relapse incidence.
Keywords: dospělí; Recurrence; Female; Adult; mladý dospělý; ženské pohlaví; Antigens, CD34; přežití bez známek nemoci; Adolescent; antigeny CD34; lidé; Hematopoietic Stem Cell Transplantation; autologní transplantace; transplantace hematopoetických kmenových buněk; příprava pacienta k transplantaci; recidiva; mobilizace hematopoetických kmenových buněk; Hematopoietic Stem Cell Mobilization; Transplantation Conditioning; transplantace kostní dřeně; Risk Factors; Remission Induction; Male; indukce remise; Young Adult; akutní myeloidní leukemie; rizikové faktory; Bone Marrow Transplantation; Disease-Free Survival; lidé středního věku; mužské pohlaví; Transplantation, Autologous; Middle Aged; mladiství; Leukemia, Myeloid, Acute; Humans